Segmentation d’image par transformée en ondelettes - Slamat Mohammed; Aziz Ben cheikh Younes; Birane Abdelkader (UNIVERSITE Amar Telidji de Laghouat.FACULTE DE TECHNOLOGIE.DEPARTEMENT D’ELECTROTECHNIQUE, 2022)
Image processing plays an important role in many fields today. In an image processing system, the most important operation is image segmentation. Until now, there is no universal image segmentation method. In this work we will talk about segmentation of images by Haar wavelet transformation by the method of (DWT), we will discover its advantages and types and what this technology offers in the field of image processing.
OPTION : instrumentation